Creative use of traditional patchwork motif in the Patchwork & Quilt workshop - Zarembo, Liene; Romančuka, Skaidrīte (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
Contemporary quilters use a wide range of Patchwork and Quilt designs and styles, from ancient and ethnic to post-modern futuristic patterns. Unusual quilting designs have increasingly become popular as decorative textiles. During the late 20th century, art quilts became popular for their aesthetic and artistic qualities rather than for functionality. Patchwork & Quilt as a form of art is very popular throughout the world. Patchwork & Quilt technology is based on stitching together, tufted fabric pieces with decorative embroidery patterns and variations on the theme of the artist's intentions. The larger design is usually based on repeat patterns built up with different fabric shapes. Patchwork is most often used to make quilts, but it can also be used to make bags, wall-hangings, warm jackets, cushion covers, skirts, waistcoats and other items of clothing. Some textile artists work with patchwork, often combining it with embroidery and other forms of stitchery. Traditional patchwork – blankets and pillows include such familiar themes as Log Cabin, Star, Pineapple, Scrap-Quilts, Bargello etc. Traditional patchwork has identifying names based on the arrangement of colors and shapes. A unique form of patchwork quilt is the Crazy Quilt. Crazy quilting was popular during the Victorian era (mid-late 19th century). The crazy quilt is made up of random shapes of luxurious fabric. The patchwork pieces are stitched together forming "crazy" or non-repeat, asymmetric compositions. Fancy embroidery embellishes the seam lines between the individual, pieced shapes. Traditions of Latvian Quilt continues at Quilt Latvian Society. Inspired by the world, Latvian artists creatively extend the style and technique-specific boundaries. Patchwork & Quilt is a process that continues to evolve and improve the selection of fabrics and innovative technological solutions and means of artistic versatility. The aim of the work – To study traditional 19th century patchwork motif and to explore the usage of Crazy Quilt motif in contemporary patchwork. Material and Methods. This paper analyses the contemporary textile artists’ quilts and traditional 19th century Crazy Quilt motif. Conclusions. The research explores traditional 19th century patchwork motif, summarizes and analyses most common visual and technological features of Crazy Quilt motif. As a result of the research, and on the basis of personal experience, authors offer the Crazy Quilt practical training (workshop) objectives and terms of reference to ensure patchwork technique practical and artistic components. Applying both – traditional and contemporary patchwork sewing techniques and combining them with textile techniques such as embroidery, crochet, textile printing and different painting techniques, there is scope for costume decoration process. The Workshop’s content is suitable for students and participants who are interested in patchwork, quilting and everything in the diverse world textile arts in the 21st century, for beginners and intermediate makers. Participants can use a Crazy Quilt for design idea and learn the easy ways how to draw chosen designs and combine patterns to create a contemporary quilt and costume elements. As a result, students obtain new knowledge, self-experience in traditional textile techniques and motivation to study textile technology.